Order Testudines: 2013 update. In: Zhang, Z.-Q. (Ed.) Animal Biodiversity: An Outline of Higher-level Classification and Survey of Taxonomic Richness (Addenda 2013) - Fritz, Uwe; Havaš, Peter (Zootaxa, 2013)
The present paper presents an update of a list of chelonian taxa published in 2011 (Fritz 2011), which generally has followed the “Checklist of chelonians of the world” by Fritz & Havaš (2007). Although chelonians (terrapins, turtles and tortoises) do not constitute a species-rich group, there exists considerable interest in their taxonomy and systematics, a fact being related with the unique morphology, the debated phylogenetic relationships and the delicate conservations status of these reptiles. Consequently, quite a number of taxonomic changes has been proposed in the past two years.